Influence of pollination mechanisms on the physical-chemical quality of strawberry (Fragaria x ananassa) cv. San Andreas - PRISCILA S. MIRANDA; ZILDA CRISTINA M. LIMA; RAQUEL PÉREZ-MALUF; ELISMAR P. DE OLIVEIRA; PAULO HENRIQUE M. MONROE; ALDENISE A. MOREIRA (Anais da Academia Brasileira de Ciências, 2025)
Abstract The objective of this study was to evaluate the physical-chemical quality parameters of strawberry fruits, cultivar San Andreas, depending on different pollination mechanisms. The study was conducted in the municipality of Barra do Choça - BA, organized into five treatments, with four replications: T1- Natural pollination (NP), T2- Natural pollination with a density of bees (NPDB), T3- Manual cross-pollination (MCP), T4- Pollination by anemophily (PA) and T5- Self-pollination (SP). For the pollination treatment with a density of bees, four hives of Iraí (Nannotrigona testaceicornis) and four hives of Jataí (Tetragonisca angustula) were placed near the strawberry plantation. After pollination of all treatments, the flowers were bagged until the development and maturation of the floral receptacle. The fruits were harvested, quantified, and subjected to evaluations to determine physical and chemical parameters. Pollination with a density of bees and natural pollination provided fruits with higher average weight, diameter, and length. Natural pollination, natural pollination with density of bees, manual cross-pollination, and anemophily pollination showed greater chromaticity in the fruits. Natural pollination and density of bees provided the best parameters (Weight, °Brix, ratio, and vit. C). Self-pollination presented the lowest averages in most of the variables analyzed.